Effect of Abstract Phonemic Complexity on Mismatch Negativity Amplitude - Najem, Fadi; White-Minnis, Letitia; Elangovan, Saravanan; Franklin, Clifford; Jamos, Abdullah (Journal of the American Academy of Audiology, 2024)
Purpose Mismatch negativity (MMN) reflects a preperceptual neurophysiological response that is generated subconsciously due to the interruption of a memory trace of ongoing sensory events in the environment. It has been widely used by researchers to understand complex perceptual mechanisms. Furthermore, it has been recommended as an objective tool to investigate disorders related to auditory cognition in hearing aid and cochlear implant users. Many researchers suggest that utilizing a larger acoustic difference between standard and deviant stimuli within the oddball paradigm will lead to a more robust MMN response. The purpose of the present study is to examine if increasing the abstract phonemic contrast between standard and deviant stimuli in the oddball paradigm leads to a more robust MMN response.Methods Fourteen young female adults participated in the present study. To ensure that the MMN response was elicited by phonemic and not acoustic differences in the stimuli, a one-to-many ratio was created for the abstract phonemic features while controlling the acoustic features when designing the oddball paradigm as described by Phillips et al. (2000). MMN amplitude was measured at the Cz and Fz electrodes in two conditions, with two trials in each condition. In condition 1, the standards and deviants differed by one distinctive feature: voicing in trial 1 (/tӕ/ was standard and /dӕ/ was deviant) and place of articulation in trial 2 (/bӕ/ was standard and /dӕ/ was deviant). In condition 2, the standards and deviants differed across two distinctive features: voicing and place of articulation. In trial 1, /pӕ/ was standard and /dӕ/ was deviant; in trial 2, /dӕ/ was standard and /pӕ/ was deviant.Results MMN amplitudes elicited by two distinctive features were significantly larger than MMN amplitudes elicited by one distinctive feature (p < 0.001). Trials 1 and 2 in each condition showed no statistical difference, and they were repeatable and highly correlated. Recordings from the Cz and Fz electrodes showed no statistical difference and were highly correlated and similar in morphology.Conclusion It is known in the literature that increasing acoustic complexity elicits a more robust MMN. The present study showed that this assumption can be extended to abstract phonemic complexity. Increasing the phonemic complexity by utilizing more distinctive features in the oddball paradigm increased the amplitude and robustness of the MMN.
Keywords: MMN; mismatch negativity; phonemic MMN; phoneme perception; MMN amplitude